Satisfaction of Saudi board internal medicine residents with the training program in central Saudi Arabia: a cross-sectional study - Alsheikh, Nejood; Alenezi, Shahad; Alshehri, Rana; Alshughaithry, Fahad; Alamri, Orjowan; Khair, Haneen; Masud, Nazish; Alonazi, Jamila (Frontiers in Education, 2024)
The Saudi Internal Medicine (IM) residency program is a four-year training program that qualifies competent physicians to provide optimal healthcare services. Residents' satisfaction is a key indicator for a program effectiveness in preparing well-trained physicians. However, no national studies have investigated the perspective of IM residents. This study assessed IM resident's satisfaction regarding the residency program in several training centers.A cross-sectional study with 194 enrolled IM residents was conducted between November 2022 and June 2023 at multiple governmental hospitals in the central region of Saudi Arabia. Data collection was done via an electronic questionnaire. The satisfaction rate was interpreted by a fivepoint Likert scale (1 "completely unsatisfied" to 5 "extremely satisfied").Out of the 184 responses, residents aged 25-27 years comprised 122 (66%) of the sample with male participants being the highest in number at 109 (59%) which was highly significant in accordance to the level of satisfaction (X2 = 10.07, p = 0.006). Additionally, 89 (54%) junior residents was found to have a significant satisfaction compared to senior residents. In total, 112 (61%) of residents would choose the same IM residency program again if they had the chance and expressed a better level of satisfaction (X2 = 101, 28, p < 0.001). Overall, the percentage of satisfied residents was around half of the sample 100 (54%). However, workload, quality of life, and teaching opportunities were among the most frequently chosen areas for improvement.The study concluded that 54% of IM residents were highly satisfied with the program in their respective training center. However, residents have excessive workload, reduced quality of life, and differing unmet learning needs.